Mouth breathing habit as an etiological factor of malocclusion: literature review: Kebiasaan bernapas melalui mulut sebagai faktor etiologi maloklusi - Eddy Heriyanto Habar; Eka Erwansyah; Khaerunnisa Bakri (Makassar Dental Journal PDGI Makassar, 2021)
Mouth breathing is one of the bad habits in the oral cavity that deviates from the normal state. The main cause of mouth breathing habit is the presence of upper respiratory tract obstruction, such as adenoid hypertrophy and allergic rhinitis. In this article, dis-cussed about the mouth breathing habit as an etiologic factor for malocclusion. By reviewing the literature, information is col-lected in accordance with the topic of the study and then synthetic. From 8 scientific articles, it is known that mouth breathing habit is an etiological factor for malocclusion, with the most common malocclusions being Class 2 malocclusion, anterior open bite, maxillary anterior teeth protrusion, and posterior crossbite. It is concluded that mouth breathing habit is one of the etiolo-gical factors for malocclusion.